Determinants of Online Waqf Acceptance: An Empirical Investigation - Hanudin Amin; Abdul Rahim Abdul Rahman; T. Ramayah; Rostinah Supinah; Masmurniwati Mohd-Aris (Pensoft Publishers, 2014)
ABSTRACT This study explores the factors influencing the acceptance of online waqf, generally termed as Islamic e-donations in Malaysia. The technology acceptance model (TAM) was used as a baseline theory. Questionnaire survey was conducted. The data of the survey were analyzed using Partial Least Square (PLS) approach. Results indicate that perceived usefulness, perceived ease of use, perceived religiosity and amount of information are instrumental in influencing one’s decision to perform online waqf. Importantly, the results of this study will extend current knowledge on technology acceptance, and online waqf particularly. The results propagate valuable insights for Islamic banking institutions to introduce online waqf in the future where the factors analyzed could be used as a guideline for better planning and implementation of online waqf. Limitations and future researches are provided.